2020
DOI: 10.3390/ani10040712
|View full text |Cite
|
Sign up to set email alerts
|

Association between Rumen Microbiota and Marbling Score in Korean Native Beef Cattle

Abstract: This study demonstrated the potential effects of the rumen microbiota on the deposition of intramuscular fat, known as marbling. Previous studies on fatty acid metabolism in beef cattle have mostly focused on biohydrogenating rumen bacteria, whereas those on the overall rumen microbiota—to understand their roles in marbling—have not been systematically performed. The rumen microbiota of 14 Korean beef cattle (Hanwoo), which showed similar carcass characteristics and blood metabolites but different marbling sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…In previous reported, rumen microbiota may affect the MS, adjusted 12th rib fat thickness, and other traits (Reddy et al, 2017;Kim et al, 2020), and its fermentation product VFAs can promote muscle growth (Kristensen et al, 2007). To investigate whether DEGs and gene co-expression modules were enriched with GWAS signals of carcass and other traits, we applied a sum-based method for GWAS signals enrichment analyses (sumGSE, https://github.…”
Section: The Enrichment Analysis Of Gwas Signalsmentioning
confidence: 99%
“…In previous reported, rumen microbiota may affect the MS, adjusted 12th rib fat thickness, and other traits (Reddy et al, 2017;Kim et al, 2020), and its fermentation product VFAs can promote muscle growth (Kristensen et al, 2007). To investigate whether DEGs and gene co-expression modules were enriched with GWAS signals of carcass and other traits, we applied a sum-based method for GWAS signals enrichment analyses (sumGSE, https://github.…”
Section: The Enrichment Analysis Of Gwas Signalsmentioning
confidence: 99%
“…Although very little is known about these bacteria, the relative abundance of the Erysipelotrichaceae family has been associated with the energy and protein metabolism of animal gut microbiota ( Bermingham et al., 2017 ). Some previous studies on beef cattle showed a positive correlation between the abundance of L7A_E11 and total VFA concentration ( Bi et al., 2018 ), and with the level of muscle marbling ( Kim et al., 2020 ). However, their role in the rumen remains unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, a higher marbling grade can obtain greater economic benefits. Particularly in Korea and Japan, producers have attempted to increase IMF to enhance the economic value of beef ( Sasaki et al, 2009 ; Kim et al, 2020 ). Experts use genetic methods to screen related genes and single nucleotide polymorphisms (SNP)( Sasaki et al, 2009 ; Kwon et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Experts use genetic methods to screen related genes and single nucleotide polymorphisms (SNP)( Sasaki et al, 2009 ; Kwon et al, 2016 ). In addition, various nutritional methods are also used, such as oil supplements, vitamin A supplementation and high-grain diet feeding ( Schmid et al, 2006 ; Gorocica-Buenfil et al, 2007 ; Pickworth et al, 2012 ; Kim et al, 2020 ). Previous studies have shown that the formation of marbling is affected by many factors, such as genetic, sexual, nutritional and management factors ( Nguyen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%